Selección de la tecnología electroquímica de remoción de metales para el tratamiento de los vertimientos provenientes de la industria de curtiembres en Villapinzón (2022)
The tannery industry is one of the most polluting sectors due to the amount of chemical substances used in its processes, the volumes of water required in these and the inadequate discharges that can generate a significant environmental impact on bodies of water. In Colombia, Villapinzón is one of the municipalities with the largest number of companies dedicated to leather production, of which less than 70% are legal, therefore, the amount of wastewater produced in this sector is worrying given that it is there where the source of the Bogotá River occurs and the discharge of these waters generates physicochemical alterations that can generate environmental degradation. Among the chemicals used are chrome salts as tanning agents which manage to stop the decomposition or degradation of the skin and thus transform it into leather by stabilizing the collagen fibers with tanning agents, from this process and because the corm it is not completely attached to the skin, water with concentrations of chromium that can be toxic to the ecosystem is discharged.